The effectiveness of physical education of student youth at the present stage - V. Banah (Journal of Education, Health and Sport, 2016)
The study was aimed at determining the state of indicators characterizing the physical condition of students, in order to draw a conclusion about the effectiveness of the current content of physical education at the present stage. Achieved this goal using a set of research methods, namely: analysis, systematization, generalization. They have been used for processed of printed and electronic sources of information. The initial and final selection of such sources was based on keywords, their corresponding abbreviations, combinations, considered the year of publication. The information obtained showed that the improvement of the organization, content, methods of physical education in higher education is impossible without establishing the effectiveness of this pedagogical process using the available results of various researchers. The main idea of these researchers was that most of the indicators that characterize the physical condition of students are different from the norm that state is regarded as an informative criterion in the effectiveness of physical education. The improvement of physical education of students is seen in the definition of effective approaches and its contents, the way in which physical education is implemented in order to increase its performance.